Process of digital transformation in medium-sized enterprises: An applied research study - Philipp Haberstock; Gabriel Weber; Christina Jägering (readbox unipress, 2018)
This working paper provides a summary of the present state of research concerning the course of digital transformations occurring in many firms globally. More specifically this paper presents performs a case study in the German firm OSRAM Opto-Semiconductors shedding lights on the specific effects that a digital transformation strategy (DTS, hereafter) has on a small-medium sized firms. Companies are facing ever changing business environments, and it is their challenge to keep up with the dynamic technical status quo. In order to do this, many (including OSRAM OS) have embraced the strategic relevance of digitalization efforts and are cur-rently working on measures to sustain their position or advance in their own markets. It has been said that digital transformation efforts often lack the momentum and sup-port needed to really move a company forward, and the aim is to assess the opportu-nities that a well-executed digital transformation brings along. The methods of analysis employed in the study include a literature research for the general, more theoretical part and empirical research on potential business impacts of a digital strategy for the company specific second part. Aforementioned research led to the conclusion that effective and efficient strategic management is key to driving a company's change efforts in the digital world.
Keywords: 650; Digitalization; organizational change; SMEs; Germany